Detection and identification of viruses by capillary isoelectric focusing - Koirala, Mukund B. (Kansas State University, 2014)
Capillary isoelectric focusing (cIEF) is one of several electrophoretic separation techniques for proteins and various other bio - molecules widely used in biochemistry laboratories. A wide range of analytes separable by the different modes of Capillary Electrophoresis (CE) includes from a small organic or an inorganic molecule to the complex bio-molecules such as protein, peptides, cell organelles, and live microorganisms (e.g. bacteria and viruses). Of the various modes of electrophoresis, Isoelectric focusing (IEF) is a good method for the separation of large amphoteric molecules such as peptides and proteins because of the attainment of overall surface charge depending up on its environment pH. This thesis mainly focuses on application of cIEF for proteins separation and viruses’ detection, which is one of the biggest concerns of human and animal health because of viral outbreak causing loss of thousands of lives and property every year. In chapter one of this thesis, the principles and mechanisms of separation of CE, cIEF, comparative advantages of dynamic coatings over static coating, and advantages of Whole Column Imaging Detection (WCID) over On - olumn Single Point Detection have been discussed. Chapter two includes experimental procedure and calculations for EOF determination. The results of cIEF experiments with standard proteins to develop calibration curve followed by UV absorbance detection of two bacteriophage viruses TR4 and T1 are presented in the chapter three. Final chapter four includes the conclusion and discussion on future direction for the project. The main motivation for this work was to develop a method which is less labor intensive and requires shorter detection time compared to traditional detection methods such as virus culture in serology (7days), polymerase chain reaction (PCR) and gel electrophoresis (6hrs to 2days). A commercially available dynamic coating reagent, EoTrol LN® copolymer used our CE experiments found to be more convenient and efficient than commonly used surface modifiers for example silane-based reagents. Preliminary determination of the pIs of these T1 and TR4 by cIEF was 3.1 ± 1.0 and 6.8 ± 1.0 respectively. The pI of viruses can differ by their strains and the phase of virus - growth. The viruses, though closely related, are easily distinguishable by their different pIs.
Keywords: Isoelectric Focusing; Bacateriophage T1; Detection; Dynamic coating; Cellular Biology (0379); Chemical Engineering (0542); Chemistry (0485); Chemistry, Agricultural (0749)